1998
DOI: 10.1063/1.120833
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coupling structure of Eu on the photoluminescent characteristics for ZnO:EuCl3 phosphors

Abstract: In this study we have synthesized ZnO:EuCl3 phosphors under various sintering atmospheres and temperatures, and investigated the effect of coupling structure of Eu in ZnO upon the photoluminescent characteristics for the purpose of searching for optimum conditions towards pure red emission. The analysis of x-ray diffraction and photoluminescence spectra measurements indicate that, for ZnO:EuCl3 phosphors sintered in vacuum, Eu exists in the host lattice as EuOCl and effectively quenches the broad-band emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 6 publications
0
29
1
1
Order By: Relevance
“…15 Recently, pure-red-emitting phosphor was synthesized using ZnO:EuCl 3 pellets sintered at 1,100°C in a vacuum. 16,17 This was the first successful attempt that demonstrated that the SA band at 530 nm can be completely suppressed in the PL emission spectrum. It suggests that the energy from generated electron-hole pairs is efficiently transferred to the Eu 3ϩ ions, giving rise to sharp, red emission peaks at 620 nm and attributed to transitions 5 D J (J ϭ 0,1) → 7 F J (J ϭ 0,1,6) of Eu 3ϩ ions.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…15 Recently, pure-red-emitting phosphor was synthesized using ZnO:EuCl 3 pellets sintered at 1,100°C in a vacuum. 16,17 This was the first successful attempt that demonstrated that the SA band at 530 nm can be completely suppressed in the PL emission spectrum. It suggests that the energy from generated electron-hole pairs is efficiently transferred to the Eu 3ϩ ions, giving rise to sharp, red emission peaks at 620 nm and attributed to transitions 5 D J (J ϭ 0,1) → 7 F J (J ϭ 0,1,6) of Eu 3ϩ ions.…”
Section: Discussionmentioning
confidence: 97%
“…Assuming that there is no back transfer of energy from 4f n electrons (justified by the long RE 3ϩ decay time it) and that the transfer rate , is much higher than , the SA broad-band emission will be suppressed or completely vanish. This model explained the Eu emission in the ZnO:EuCl 3 phosphor, 16,17 where the Eu exists in the ZnO lattice as the tetragonal phase of EuOCl and effectively transfers energy to 4f electrons of Eu 3ϩ ion, eliminating the broad-band emission of the ZnO host. We believe that a similar center, TmOCl, with tetragonal phase is responsible for the PL emission of Tm 3ϩ shown in Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…After all the samples are annealing at 900˚C by 20 h. The ZnO:Eu 3+ samples thus obtained were structurally characterized by X-ray diffraction (XRD) technique using a Philips PW 1800 diffractometer with Cu kα radiation (1.5406 Å), XPS method was used to verify the Zn-O, Eu-O and O1s bonding energies (BE), the photoluminescence (PL) of the ZnO:Eu 3+ samples was studied by means of a spectrofluorometer FluoroMax-P that uses a xenon lamp as excitation source, The wavelength excitation was of 270 nm, and finally, the morphology of the ZnO:Eu 3+ powders was recorded using a scanning electron microscopy SEM) JEOL JSM 840 A. Figure 1 shows the X-ray diffractograms of the ZnO:Eu 3+ powders as a function of the Eu 3+ ion concentration and annealing at 900˚C by 20 h. From the XRD patterns, can be observed that all the diffraction peaks can be indexed to the majority phase hexagonal wurtzite tipe ZnO structure for all samples (JCPDS card #89-(102), moreover, for all the Eu 3+ ion concentrations a little peak at 2θ = 28.4˚ is observed, which is attributed to the (210) plane of the Eu 2 O 3 minority phase (JPDS card #86-2476), Park et al [27] reported diffraction peaks due to Eu 2 O 3 after annealing the Eu 3+ doped ZnO at temperatures higher 1000˚C in air and vacun conditions, no diffraction peaks were detected from other impurities. However, the intensity of the (101) peaks decrease with the increase in the Eu 3+ concentration which create some disorder in the ZnO structure.…”
Section: Methodsmentioning
confidence: 99%